2007
DOI: 10.1007/s11102-007-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Five years follow-up of invasive prolactinomas with special reference to the control of cavernous sinus invasion

Abstract: About three-fourths of prolactinomas with CS invasion can be effectively controlled not only with regard to tumor volume disappearance but also in serum PRL normalization. Residual tumor in the CS areas with PRL normalization and no pressure symptoms can be treated with low-dose of bromocriptine so as to achieve long-term tumor volume control and endocrine control. Great attention should be paid to CS residual tumors accompanying the empty sella, especially in cases with optic chiasmal herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
2
26
0
1
Order By: Relevance
“…Previous studies have demonstrated that volume decrement on initial MRI or prolonged medication may result in further volume decrement, and our findings also supported these results [12,15,19]. In addition, our results suggest that tumor contrast enhancement profiles after medication may be another predictor of the radiologic response rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have demonstrated that volume decrement on initial MRI or prolonged medication may result in further volume decrement, and our findings also supported these results [12,15,19]. In addition, our results suggest that tumor contrast enhancement profiles after medication may be another predictor of the radiologic response rate.…”
Section: Discussionsupporting
confidence: 90%
“…Even after patients had achieved radiologic remission, they had to receive DA to maintain normal endocrine function [12,13]. The causes of increased prolactin after radiologic remission are suggested as follows: 1) prolactin secretion from residual tumors in the cavernous sinus or other areas, despite their absence in the MR images; and 2) injury to the hypothalamic-pituitary-axis in the process of the empty sella formation [12]. Considering these findings, the prolactin normalization remains an important and easily assessable end-point.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor diameter [16], or volume calculated by Tada formula [7,17] was considered as the main evaluation indicator for tumor size. However, tumor volume of pituitary adenoma calculated by Tada formula would generate great error because of the irregular shape and the multi-direction growth of pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Residual cavernous sinus lesions in some patients may remain even after continuous drug therapy. 28,46,55,56 …”
Section: Discussionmentioning
confidence: 99%